Análisis de los problemas en el Servicio de Internet hacia los clientes home de la Empresa Grupo Internet Para Todos de la ciudad de Babahoyo. - Andaluz Bajaña, Patricia Pilar (2017)
The "Grupo Internet para Todos" is a professional company located in the province of Los Ríos, Babahoyo city, founded under the principles of ethics and values ​​that seeks the satisfaction of its customers, working hard constantly updating in knowledge and technological equipment of to provide the best internet service, in order to optimize the quality of life for all customers and facilitate access to information, by providing digital services composed of a strong technological innovation and a human resource highly qualified and motivated, contributing to the development of the Information Society in the country. Being one the leading organization in technological innovation of the province, promoting relations with each and every one of its clients. Thus, it is necessary to analyze the existing problems in the internet connectivity service to customers, with the purpose of offering an adequate service, identifying problems and establishing components and forms of action to give the possible solution to the problems presented . Given the current situation, computer systems are advancing and are of vital importance for the development and productivity in companies. The internet group for all companies dedicated to provide internet, therefore it is necessary to maintain the necessary security, take specific measures to sponsor better expertise and improve the quality of service efficiently and provide a better quality service to its customers, so that is exposed to suffer any failure in the service, which can cause inconvenience with its customers. These problems can be given as hardware (outdated equipment, distribution of equipment for each node of the Internet service and software such as viruses, worms, malware that become sensitive to the data networks of the Internet service).